Answer:
First angle = [tex]90^{\circ}[/tex]
Secomd angle = [tex]40^{\circ}[/tex]
Thirsd angle = [tex]50^{\circ}[/tex]
Step-by-step explanation:
Let the first angle be x------------(1)
Then the second angle is 50° less than the first angle
Then the second angle will be x -50------------(2)
The third angle is 40° less than the first angle
Then the angle will be x - 40------------(3)
We know that, according to angle sum property , the sum of all the three angle will be 180 degrees
So adding all the 3 angles,
[tex]x + (x -50^{\circ}) +(x -40 ^{\circ}) = 180^{\circ}[/tex]
[tex]x + x -50^{\circ} +x -40 ^{\circ} = 180^{\circ}[/tex]
[tex]3x -90^{\circ} = 180^{\circ}[/tex]
[tex]3x = 180^{\circ} +90^{\circ}[/tex]
[tex]3x = 270^{\circ}[/tex]
[tex]x = \frac{270^{\circ}}{3}[/tex]
[tex]x = 90^{\circ}[/tex]
Now the second angle is
=> [tex]x -50^{\circ}[/tex]
=> [tex]90 ^{\circ} -50 ^{\circ}[/tex]
=> [tex]40^{\circ}[/tex]
The Third angle is
=> [tex]x- 40^{\circ}[/tex]
=>[tex]90^{\circ} - 40^{\circ}[/tex]
=> [tex]50^{\circ}[/tex]